La magia nelle leges. Questioni strutturali - Daniela Fruscione (Filologia Germanica, 2025)
Beginning in the sixth century the Germanic peoples who established kingdoms in the western parts of the old Roman Empire enacted several law codes. The codes, composed in Latin, were partly influenced by Roman law. The early medieval decrees tell us what was prohibited and what was designated as magic, disclosing some magic practices like divination, storm rising, the use of ligatures and veneficium. However, the decrees do not always indicate the context of the forbidden acts. The article does not focus on the practice of magic but rather on the concerns of the authorities as to the provisions on magic contained in the laws. It will be shown that in the leges that were basically designed to assure both the wholeness or physical integrity of the person, and the safety of property, the use of magic is not punished as a religious offence, but rather for its destabilizing aspect regarding the social, political and economic order. The lawgiver’s priority is not simply the material damage caused by magic practices, but also the damage caused by false witchcraft accusations, which can ruin the reputation of a woman and of her family group. Finally, the Romano-Germanic laws show that, beyond the damage caused to its subjects, the king feels offended by magic as an antagonistic instrument of power and social control. Thus, from early medieval laws, it is possible to observe the formal expression of areas through which public concerns over the practice of magic operated.